Corporate governance and audit process - Lim, Chee Yeow (2015)
Recent studies on whether the provision of non-audit services impairs audit quality document mixed results, depending on the proxy for auditor quality used. We posit that the effect of non-audit fees on audit quality is conditional on auditor industry specialization in that audit quality is less likely to be impaired in the case of industry specialist auditors providing non-audit services. Our premise is that industry specialist auditors are more likely to be concerned about reputation losses and litigation exposure, and to benefit from knowledge spillovers from the provision of non-audit services. We find some evidence that audit quality (as measured by increased propensity to issue going-concern opinion, increased propensity to miss analysts’ forecasts, as well as higher earnings-response coefficients) is less likely to be reduced for firms that acquire non-audit services from industry specialist auditors compared to non-specialist auditors. Implications are discussed.